Kesan interaksi di antara rekabentuk sistem pampasan dengan keadilan distributif terhadap kepuasan kerja - Muhamad Faizil, Muhamad Faisal (Universiti Malaysia Sarawak (UNIMAS), 2005)
Compensation literature has show that pay design system may affect individual attitudes and behaviors. The effect of pay design issues on job satisfaction does not clear if distributive justice is present in organization. This study used qualitative and quantitative research designs as a procedure for collecting and analyzing the data. The outcomes of multiple regression analysis showed that distributive justice played a moderating role in the relationship between pay design system and job satisfaction. These findings are consistent with compensation literature. This study has significant implications to theory, research methodology and human resources practitioners. In term of theoretical contribution, these findings showed that distributive justice played important rolls that can influence the compensation management. Meanwhile, this study also used to support human resource manager to design the compensation system that can influence the employee's attitude and behavior.